Analisis Pengaruh PDRB Perkapita dan Rata-Rata Lama Sekolah terhadap Indeks Pembangunan Manusia (IPM) di Provinsi Kalimantan Selatan - Indy Pratiwi; Albert Samuel Sinaga; Sinsi Setiawati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The quality of human resources is an important aspect in regional development, which is reflected through the Human Development Index (HDI). HDI is influenced by various factors, including the economic conditions and education of the community. This study aims to analyze the effect of Gross Regional Domestic Product (GRDP) per capita and Average Length of Schooling (RLS) on HDI in South Kalimantan Province. The data used comes from the Central Statistics Agency (BPS) with a coverage of 13 regencies/cities during the period 2018 to 2023. The analysis method used is multiple linear regression with the help of R Studio software. The results of the study show that both GRDP per capita and RLS have a significant effect on HDI, both simultaneously and partially. The resulting model has an adjusted R² value of 0.8627, which indicates that 86.27% of the variation in HDI can be explained by these two variables. The classical assumption test including linearity, conditional zero error expectation, absence of multicollinearity, autocorrelation, homoscedasticity, and residual normality shows that the model used has met all the criteria as the Best Linear Unbiased Estimator (BLUE). Thus, this regression model is valid for use in estimating and making inferences on the factors that influence the HDI in South Kalimantan Province. This finding confirms that increasing education and economic growth are strategic steps in accelerating human development in South Kalimantan.